Seni Dan Desain Sang Primadona, Seni Kriya Sang Penyelamat - -, Dharsono (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
As the dichotomy emerged in 1970s art , artists in the tradition of "fine art " artist called ,were the perpetrators in the category of " craft " so-called artisan or craftsman .Especially painting get a superior position , because of the success of the artist paintingthe west in the seat as part of a " liberal art " activities that reflect part of intelegtualitas ,being " craftmanship " merely " mechanical art " Then marginalized craft and fine art ofthe prima donnaFurther development , the emergence of trichotomy of art , design and craft ( the 1980s) , the more visible and tangible . Craft positions below , even debased or diinferiorkanby fine art or design . So the design of the prima donna .But what's the reality ? ! ...... When the Indonesian economic crisis of 1998, the craft isthrown down , the craft is thrown into marginal - hall , in reality it is instrumental tocreating jobs and even contribute significantly in moving the economy in layer " grassroot " . Even with the collapse of capital-intensive , it sparked the birth of entrepreneursto move the craft -based industries such as in Jepara , Cirebon , Surakarta . Kriyabecame the savior .